2007
DOI: 10.1530/rep.1.01089
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone inhibits matrix metalloproteinase-1 production in human endometrial stromal cells in vitro

Abstract: Androgen receptor (AR) is reported to be expressed in human uterine endometrium, but not much information is available on the role of androgens in human endometrium. The purpose of this study is to investigate the role of androgens in the regulation of matrix metalloproteinase (MMP)-1, which is one of the important MMPs for menstruation and embryo implantation in human endometrium. Human endometrial stromal cells (HESCs) were obtained from human endometrium by enzymatic dissociation method. Purified HESCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
1
11
0
2
Order By: Relevance
“…Androgen plays an important role in morphological and functional changes of the human endometrium, for example, testosterone can inhibit the expression of MMP-1, a gene that has important roles in implantation and pregnancy [27]. In this study, we studied the effect of androgen on NSSR1 expression in the uterus using testosterone and androgen antagonist, flutamide.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen plays an important role in morphological and functional changes of the human endometrium, for example, testosterone can inhibit the expression of MMP-1, a gene that has important roles in implantation and pregnancy [27]. In this study, we studied the effect of androgen on NSSR1 expression in the uterus using testosterone and androgen antagonist, flutamide.…”
Section: Discussionmentioning
confidence: 99%
“…A portion of each endometrial specimen in the proliferative phase was confirmed histologically according to the day of the menstrual cycles. ESCs were purified by the standard enzyme digestion method as described previously (21,22). ESCs were cultured in DMEM/F-12 medium supplemented with 10% fetal calf serum (FCS; HyClone), 100 IU/mL penicillin, and 100 mg/mL streptomycin (Invitrogen) at 37 C under an atmosphere of 5% CO 2 in air.…”
Section: Materials and Methods Tissue Collection And Culture Of Cellsmentioning
confidence: 99%
“…The ESCs were purified by the standard enzyme digestion method as described previously (20,21). The purity of ESCs was determined by morphology and by immunohistochemical staining as described previously (22,23) with markers specific to ESCs (vimentin).…”
Section: Materials and Methods Tissue Collection And Culture Of Escsmentioning
confidence: 99%